Mathematical Education and Developing the Emotional and Social Competencies of the Child in Pre-primary and Primary Education in Slovakias - Iveta Scholtzová; Edita Šimčíková (Ignatianum University Press, 2019)
Mathematical education at the pre-primary stage sets out its aims which are predominantly focussed on the area of developing the cognitive side of the child's personality. This area becomes the focus of relevant curricular documents for mathematical education, on the one hand, and influences the actual teaching of mathematics in practice, on the other. Meaningful and effective cross-curricular mathematical education opens a new space for developing the emotional and social skills of the child. The above aspect of mathematical education has the potential to become a determining factor in creating a positive attitude towards mathematics.